THE INFLUENCE OF WORK CULTURE AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE AND ITS IMPACT ON SERVICE QUALITY IN THE TECHNICAL IMPLEMENTING UNIT OF THE BABULU PUBLIC HEALTH CENTER (UPT PUSKESMAS) - Alif Patul Ulumi; Sri Rochani Mulyani (Jurnal Scientia, 2023)
This study aims to examine the influence of work culture and work discipline on service performance at UPT Puskesmas Babulu mediated by employee performance. The approach used in this research is a quantitative approach. The sample used in this study were employees of the Babulu Public Health Center, Penajam Paser Utara Regency, East Kalimantan, a total of 67 employees. The research data was obtained from the results of filling out the questionnaire and analyzed using the SEM PLS analysis technique with the help of the SmartPLS program. The results of this study indicate that work culture and work discipline have a significant effect on the service performance of UPT Puskesmas Babulu either directly or mediated by employee performance. High employee work discipline supported by a good work culture will improve employee performance which will further improve the service performance of UPT Puskesma Babulu.